MENUJU KEPUASAN LAYANAN AKADEMIK PERGURUAN TINGGI - Mubasit, Mubasit (BINA' AL-UMMAH, 2015)
Quality of academic services is important for higher education institutions. This service reflects the quality of that institution. The assessment of whether the institution achieves good quality is determined by its users’ perception. Therefore, achieving academic service satisfaction constitutes long term strategy requiring financial and human resources. This paper proposes some strategies for higher education institutions to achieve users’ satisfaction. These include superior customer service; unconditional service guarantees or extraordinary guarantees; complaint handle; institutional achievement enhancement; and quality function deployment (QFD).